If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 2(4a + 2) Reorder the terms: 16 = 2(2 + 4a) 16 = (2 * 2 + 4a * 2) 16 = (4 + 8a) Solving 16 = 4 + 8a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8a' to each side of the equation. 16 + -8a = 4 + 8a + -8a Combine like terms: 8a + -8a = 0 16 + -8a = 4 + 0 16 + -8a = 4 Add '-16' to each side of the equation. 16 + -16 + -8a = 4 + -16 Combine like terms: 16 + -16 = 0 0 + -8a = 4 + -16 -8a = 4 + -16 Combine like terms: 4 + -16 = -12 -8a = -12 Divide each side by '-8'. a = 1.5 Simplifying a = 1.5
| Y=-3mx | | 2(5-3x)+9x=28-3x | | -14=w/3-4 | | t=16t^2+500 | | 3x^2-12x+60=0 | | 1-((1/3)t^(-2/3)) | | 5x-8=40-3x | | 3(m+8)=-6 | | 19x+19x+30x-15=325 | | -7=5+2u | | X^2+2*X+i=0 | | 3x+5=22x+9 | | Lnx=1.8+ln(0.1) | | 241=71-u | | 16n+4=15n-18 | | X=400-4/5 | | t-t^(-2/3)=0 | | 30=2*y | | -3f-4f+7j-9j= | | −7/8≤m−13/8 | | ax+8=3x+c | | n+(n+2)+(n+4)=246 | | X/4=34 | | t-t^(1/3)=0 | | 25+3x+25+3x+25+3x+25+3x=112 | | y=x^4-18x^2 | | 30+10(50-7g+2)=-70g+21+500 | | 1+2(6w-6)=-3(3w-1)+3w | | 7(b-5)+12=15 | | 2y-8+6(2y+1)=-2(y+4) | | 5h=3h+12 | | 6.5/9 |